Management of congenital talipes equinovarus by Ponseti technique and percutaneous needle tenotomy - Mukkaram, Mohammed; Awais, Daniya; Razvi, Ali (International Journal of Research in Orthopaedics, 2024)
Background: This study evaluates the Ponseti technique combined with percutaneous needle tenotomy for treating congenital talipes equinovarus (CTEV), or clubfoot, assessing efficacy, complications, and outcomes. Conducted at a tertiary medical center in Hyderabad from 2021 to 2024, it included patients of all ages presenting with CTEV. Methods: This is a prospective and retrospective study. The Ponseti method, a conservative approach involving serial casting and gentle foot manipulation, was applied, with percutaneous needle tenotomy used for achilles tendon lengthening when necessary. Compared to traditional surgical methods, this minimally invasive approach is associated with fewer complications and improved correction rates. Patients were assessed using Pirani scores, with data on cast numbers, tenotomy needs, and relapses. Results: The study demonstrated significant efficacy, particularly when treatment began early, reducing the number of casts required. Needle tenotomy, preferable over blade tenotomy, was particularly effective in India and among patients from lower socioeconomic backgrounds, proved more effective than blade tenotomy. The approach was associated with fewer complications and better correction rates. Conclusions: The Ponseti technique is an effective, accessible, and economical option with minimal complications. Early diagnosis and intervention were found essential for optimal outcomes. Further research is suggested to refine treatment protocols for older children and severe deformities.